Human Resource Performances of The Plantation and Workshop Divisions in The Tractor Readiness Service For The Operation of Sugarcane Plantation at PT Sweet Indo Lampung - Olivia Esteevani Wibisono; Lestari Rahayu Waluyati; Dwidjono Hadi Darwanto (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2017)
The aims of this paper are to investigate the human resource performances at the workshop division in fixing damage tractors and to determine factors influencing their performances, and also to analyze the human resource performances on the plantation division in operating tractors to support the operation of sugarcane plantation. The survey method was conducted to collect primary data from the plantation and workshop divisions employees of PT Sweet Indo Lampung (PT SIL). Likert scale was applied to measure and determine variables of human resource performance and other relevant variables. Multiple linear regression models were used for the analysis measurement of human resources performances. The results show that human resource performances in the workshop and plantation divisions to operate tractors are in good category, but it still has to be improved. This includes the timelines to finish the work, obedience and loyalty of the employees, work planning and ability to manage the work. The factors that have positive influence on human resource performances are compensation, work environment, work relationship, and employee potential. The factor that has negative influence is expectation in developing performance. The longer time needed to repair the tractors was caused by the spare parts stock, number of mechanics that can handle the tractor, the workers skill and teamwork. Factors that cause damage on tractors are lack of maintenance, sloping area in sugar cane plantation, and lack of operators skill.